Tracking SARS-CoV-2 seropositivity in rural communities using blood-fed mosquitoes: a proof-of-concept study - Krajacich, Benjamin J.; Samaké, Djibril; Dao, Adama; Diallo, Moussa; Sanogo, Zana Lamissa; Yaro, Alpha Seydou; Zeguime, Amatigue; Poudiougo, Josué; Cissé, Kadiatou; Traoré, Mamadou; dit Assitoun, Alassane; Faiman, Roy; et al. (Frontiers in Epidemiology, 2023)
The spread of SARS-CoV-2 cannot be well monitored and understood in areas without capacity for effective disease surveillance. Countries with a young population will have disproportionately large numbers of asymptomatic or pauci-symptomatic infections, further hindering detection of infection. Sero-surveillance on a country-wide scale by trained medical professionals may be limited in a resource limited setting such as Mali. Novel ways of broadly sampling the human population in a non-invasive method would allow for large-scale surveillance at a reduced cost. Here we evaluate the collection of naturally blood-fed mosquitoes to test for human anti-SARS-CoV-2 antibodies in the laboratory and at five field locations in Mali. Immunoglobulin-G antibodies to multiple SARS-CoV-2 antigens were readily detected in mosquito bloodmeals by bead-based immunoassay through at least 10 hours post-feeding (sensitivity 0.92 [0.78-1] (mean and 95% CI) and specificity 0.98 [0.88-1]), indicating that most blood-fed mosquitoes collected indoors during early morning hours (and likely to have fed the previous night) are viable samples for analysis. We found that reactivity to four SARS-CoV-2 antigens rose during the pandemic from pre-pandemic levels. Crude seropositivity of blood sampled via mosquitoes was 6.3% in October/November 2020 across all sites, and increased to 25.1% overall by February 2021, with the most urban site reaching 46.7%, consistent with independent venous blood-based sero-surveillance estimates. We have demonstrated that using mosquito bloodmeals, country-wide sero-surveillance of human diseases (both vector-borne and non-vector-borne) is possible in areas where human-biting mosquitoes are common, offering an informative, cost-effective, and non-invasive sampling option.